2021
DOI: 10.3389/fneur.2021.671915
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Intracranial Aneurysms in Small Peripheral Vessel Segments—Efficacy and Intermediate Follow-Up Results of Flow Diversion With the Silk Vista Baby Low-Profile Flow Diverter

Abstract: Background and Purpose: Low-profile flow diverter stents (FDS) quite recently amended peripheral segments as targets for hemodynamic aneurysm treatment; however, reports on outcomes, especially later than 3 months, are scarce. This study therefore reports our experience with the novel silk vista baby (SVB) FDS and respective outcomes after 8 and 11 months with special respect to specific adverse events.Materials and Methods: Forty-four patients (mean age, 53 years) harboring 47 aneurysms treated with the SVB b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Major complications ranged from 1.6% to 2.3%. 14-16,28 Moreover, there were no other complications related to the treatment, and 11 patients from 24 had complete occlusions at their 3-month follow-up.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Major complications ranged from 1.6% to 2.3%. 14-16,28 Moreover, there were no other complications related to the treatment, and 11 patients from 24 had complete occlusions at their 3-month follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Of those, 2 were true PICA aneurysms (2/173; 1.2%). 13-16 The occlusion rate varied from 57.1% to 76% in the latest follow-up angiogram (O'Kelly Marotta C-D or Raymond-Roy I-II). Major complications ranged from 1.6% to 2.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FD placed at the neck of the aneurysm reduces blood flow to the aneurysm by diverting the flow to the main artery and induces thrombosis [ 5 , 11 13 ]. FDs have been used increasingly due to its efficacy and safety profile [ 14 , 15 ]. A recent meta-analysis by Briganti et al [ 16 ] indicated that FD stenting of intracranial aneurysms achieved a good percentage of occlusion 81.5% with a low incidence of major complications (mean 8.3% range 0–23).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the surface modification of the p48MW HPC the architectures of the SVB and the p48MW are largely comparable. Nevertheless, recent reports indicate that each of the devices may have specific suitability profiles for different cerebrovascular segments, and that time span to aneurysm occlusion post implantation may differ between both devices [ 8 , 18 ]. Therefore, the aim of this study is (a) to report our experiences with both devices for treatment of distally located cerebral aneurysms specifically focusing on their eligibility for different locations and (b) to provide a first comparison of the efficacy, clinical outcomes and angiographic outcomes after implantation of the SVB and the p48MW HPC.…”
Section: Introductionmentioning
confidence: 99%